A Column-Generation Approach for a Short-Term Production Planning Problem in Closed-Loop Supply Chains - Florian Sahling (BuR - Business Research, 2013)
We present a new model formulation for a multi-product lot-sizing problem with product returns and remanufacturing subject to a capacity constraint. The given external demand of the products has to be satisfied by remanufactured or newly produced goods. The objective is to determine a feasible production plan, which minimizes production, holding, and setup costs. As the LP relaxation of a model formulation based on the well-known CLSP leads to very poor lower bounds, we propose a column-generation approach to determine tighter bounds. The lower bound obtained by column generation can be easily transferred into a feasible solution by a truncated branch-and-bound approach using CPLEX. The results of an extensive numerical study show the high solution quality of the proposed solution approach.
urn:nbn:de:0009-20-36463
Keywords: 650; closed-loop supply chains; column-generation; remanufacturing; Produktionsplanung; Betriebliche Kreislaufwirtschaft; Lieferkette; Branch-and-Bound-Verfahren